2014
DOI: 10.1155/2014/746705
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis Patients in the Postmenopausal Period: Pre- and Postmenopausal Factors Influencing Postmenopausal Health

Abstract: Objective. To evaluate patients' health status and the course of endometriosis from the premenopausal to the postmenopausal period and evaluate influencing factors that may be relevant. Methods. Questionnaire completed by 35 postmenopausal women in whom endometriosis had been histologically confirmed premenopausally. Correlation and regression analyses were carried out to identify factors relevant to their postmenopausal health status. Results. Overall, there was clear improvement in typical endometriosis symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
8
0
2
Order By: Relevance
“…Due to the lack of large cohort studies, the prevalence of endometriosis is still unknown [ 3 ], but it is estimated that 10 to 15 percent of women in the reproductive age are affected by the disease [ 4 ]. As endometriosis is regarded to be a condition of the premenopausal woman, its peak of prevalence coincides with a woman's reproductive period [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of large cohort studies, the prevalence of endometriosis is still unknown [ 3 ], but it is estimated that 10 to 15 percent of women in the reproductive age are affected by the disease [ 4 ]. As endometriosis is regarded to be a condition of the premenopausal woman, its peak of prevalence coincides with a woman's reproductive period [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that endogenous estrogen even at low levels is a risk factor for some women. Endometriosis lesions contain aromatase and estrogen may stimulate prostaglandin-E synthesis, which in turn increases aromatase activity in lesions (22,(24)(25)(26)(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Haas et al performed a retrospective analysis of 42,079 women with surgically confirmed endometriosis in Germany and they found 1,074 (2.55%) cases in the climacteric age group (55–95 years) [8]. Moreover, in a subsequent study, Haas et al [9] found that physical fitness and freedom from physical restrictions, a good social environment and psychological care in the postmenopausal period lead to a remarkable improvement in pain, dyspareunia, and influence on sexual life in women with endometriosis.…”
Section: Introductionmentioning
confidence: 99%